Early auroral photography and observations at the Sodankylä Geophysical Observatory in Finland, 1927–1929 - Nevanlinna, Heikki; Tanskanen, Eija I. (Copernicus Publications, 2025)
In Finland, auroral photography started in 1927 at the Sodankylä Geophysical Observatory (SGO) with the initiative of famous Norwegian scientist Carl Störmer. In less than 2 years about 600 photographs of auroras were taken at Sodankylä. Some of the images were obtained simultaneously at auxiliary stations for parallactic determinations of the height of auroral arcs. Most of the pictures of auroras were lost in the destruction of the SGO during the war in 1944. About 200 images were rescued in the archive of the Finnish Meteorological Institute, where they were recently found. These pictures of auroras are the first ones taken in Finland. These photographs are now digitized and archived in the SGO. During the polar year period 1932–1933, auroral photography was mostly discontinued, but visual observations of auroras were made instead at several sites in Lapland. The main sources of information about the history of auroral images are handwritten notebooks of Eyvind Sucksdorff for 1927–1929. They contain relevant data for each photograph (date, exposure time, orientation of camera etc.). In Appendix A there are tables showing the dates of rescued auroral photographs as well as the lost ones. In Finland, Sucksdorff's contribution to studies of auroras was a pioneering effort with minima